2018
DOI: 10.1097/coh.0000000000000489
|View full text |Cite
|
Sign up to set email alerts
|

Ethical issues in HIV remission trials

Abstract: Purpose of reviewSeveral promising experimental pathways exist for long-term control of HIV in the absence of antiretroviral therapy (HIV ‘remission’) and are now being tested in early clinical studies. These studies can be invasive and pose a host of distinctive risks to participants, as well as to nonparticipants, especially to participants’ fetuses, and sexual partners.Recent findingsEthical analyses of these studies have mainly focused on the risks to study participants. They recommend, and some investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…Scalability Considerations : Bioethicists, researchers, and community members have recognized that scalability of interventions is potentially a key factor by which to judge the social value of HIV cure research strategies [ 3 , 7 , 28 , 29 , 45 , 65 , 66 ]. This aligns with the rationale for advancing translational research related to an HIV cure [ 45 , 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Scalability Considerations : Bioethicists, researchers, and community members have recognized that scalability of interventions is potentially a key factor by which to judge the social value of HIV cure research strategies [ 3 , 7 , 28 , 29 , 45 , 65 , 66 ]. This aligns with the rationale for advancing translational research related to an HIV cure [ 45 , 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Use of Placebos : As in other research settings, determining the ethical and scientific appropriateness of placebo-controlled trials in HIV cure research can be complex [ 7 , 9 ]. After extensive deliberation, a multi-disciplinary group of HIV cure experts concluded that placebo arms should be used where necessary and appropriate to confirm scientific validity of trials [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, scalability of Interventions will be a critical Integrative BSSR topic that will determine the societal value of HIV cure regimens . Better knowledge about cost‐effectiveness and performance benchmarks (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…This impact can be substantial and raise ethical quandaries, as two recent examples illustrate. Participants in ongoing HIV curerelated studies with an interruption of antiretroviral therapy may transmit the virus to fetuses and sexual partners when HIV concentration in body fluids increases after that interruption (4). A report by a US National Institute of Allergy and Infectious Diseases planning committee recently recommended against challenge studies for Zika vaccine candidates in part because such studies would risk transmission to fetuses, sexual partners, and even people bitten by the same mosquitos who bit study participants (5).…”
Section: Risks To Research Bystandersmentioning
confidence: 99%